Non-dimensional solutions for the stabilising piles in landslides in layered cohesive soils considering non-linear soil–pile interactions. Issue 8 (10th August 2022) - Lei, Guoping; Su, Dong; Cabrera, Miguel Angel
Abstract : The pile response is of great importance to the effectiveness of a row of piles used as a landslide mitigation method. However, the current classifications of the pile responses and failure modes do not consider the effects of soil displacement and the relative pile rigidity. An attempt is made in this paper to improve this using a non-dimensional model based on simplified ground consisted of two layers of cohesive soils. A hyperbolic p – y model is adopted to consider non-linear soil reactions. The calculations of three case histories show that the proposed model predicts the pile responses well. The dependencies for obtaining a pile response with maximum pile resistance have been identified and the influencing factors have been examined. The efficacy of the proposed approach has been demonstrated by the satisfactory result that it achieves in reproducing the more complex three-dimensional finite-element analyses. The application of the non-dimensional solutions indicates that it can increase the efficiency of the preliminary pile design.